Synergizing Online Business and Human Rights: A Holistic Analysis - Salsabila Anissa; Noor Fatimah Mediawati; Nurhayati (Proceedings of The ICECRS, 2023)
This data article presents a systematic data retrieval process on lens.org, where a search for "Online Business" and "Human Rights" keywords yielded 63,504 documents. Filtering by document type, we focused on "Journal Article" and "Conference Proceeding," resulting in 49,616 relevant documents. In the final step, further refinement by the subject matter "Law" identified 2,639 documents. The collected data serves as a valuable resource for researchers and authors seeking to explore the intersection of online business and human rights in academic literature. This comprehensive dataset streamlines the research process and fosters in-depth literature reviews in this critical field.Highlights : Vast Data Resource: The data retrieval process yielded a substantial dataset of 2,639 journal articles and conference proceedings, providing researchers with a wealth of information on the intersection of online business and human rights. Streamlined Research: This comprehensive data collection process simplifies literature review tasks, enabling quick access to relevant articles, ultimately expediting research in the field. Legal Focus: By filtering for the "Law" subject matter, the dataset is particularly valuable for those examining the legal aspects of online business and human rights, facilitating focused and in-depth investigations. Keywords: Online Business, Human Rights, Data Retrieval, Literature Review, Law